(untitled) (Itinera, 2022)
Inevitably associated with perceptual or image theories, thematized through its psychologization or through a symbolic-anthropological perspective, color has often been taken away from one of its possible stories. The present contribution attempts to investigate this path in which color in modernity has become the pretext for a rewriting, often of rupture, of reality as in the case of the translations from the Greek of Hölderlin and the poetology of Rimbaud up to the Bauhaus aesthetics, but also its opposite: a sort of consolidation of social clichés as Abraham Moles (speaking of “sentimental chromatism”) and Jean Baudrillard (interpreting color as a mere semiotic value independent of the taste and perception of the subject) have shown in different but complementary ways.